Kaili structured sonic and movement systems, Kreasi Baru, and the assertion of a national presence through the performing arts in Central Sulawesi - Santaella, Mayco A. (2016)
This dissertation investigates Kaili structured sonic and movement systems, postindependence inception of the performing art genres of music and dance, and new approaches to compositions and choreographies during the reformation era in Central Sulawesi. Ethnomusicological studies of Indonesian traditions and national cultural policies have concentrated largely on Javanese and Balinese forms of expression.While some studies of periphery regions have documented traditions and the application of national policies, an ethnomusicological and ethnochoreological discourse of marginalized communities in Central Sulawesi is almost non-existent. In order to contribute to this discourse,this dissertation utilizes a tripartite analysis. First,is the analysis of pre-independence Kaili sonic and movement heritages; secondly,the development of nationalized aesthetics in the post-independence kreasi baru (new creation) genre from 1945 to 1998; and thirdly an analysis of new approaches to staged presentations contesting kreasi baru during the reformation era (r.1998-present).This dissertation is the product of ethnographic research carried out in Central Sulawesi during annual field research since 2005. Each chapter presents an analysis of case studies of both individual and ensemble approaches to the presentation and representation of Kaili culture. The investigation scrutinizes a Kaili heritage of sonic and movement systems as participatory components of larger events. It also investigates the inception of post-independence music and dance genres depicting nationalized aesthetics, as well as a post-national contestation of kreasi baru through new compositional and choreographical approaches. I argue that these three forms namely the heritage, the national and the post-national are part of the present cultural matrix that represents Kaili identity through performance.